2017
DOI: 10.17268/sci.agropecu.2017.04.11
|View full text |Cite
|
Sign up to set email alerts
|

Effect of essential oil of Cymbopogon citratus in the physicochemical properties of quitosan films

Abstract: ResumenSe investigó el efecto de la incorporación de aceite esencial de zacate limón (Cymbopogon citratus), en concentraciones de 0, 200 y 400 ppm, en las propiedades fisicoquímicas (espesor, humedad, solubilidad, permeabilidad al vapor de agua, color, transparencia) y mecánicas (resistencia a la tensión y elongación) de películas de quitosano a dos concentraciones (1 y 3%). Los resultados mostraron un efecto significativo (p ≤ 0,05) en los valores del espesor de las películas a las dos concentraciones de quit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 29 publications
0
1
0
Order By: Relevance
“…In a recent study, Kerch and Korkhov [44] reported low molecular chitosan films values of TS ≈ 40 MPa; while %E, for low molecular weight films were 15%. Despite that, Vázquez-Briones and Guerrero-Beltrán [45] reported values of TS ≈ 5 MPa and %E = 29% for low molecular weight chitosan films, indicating that these values are related with chitosan concentration (%) employed for films elaboration.…”
Section: Mechanical Properties Evaluationmentioning
confidence: 90%
“…In a recent study, Kerch and Korkhov [44] reported low molecular chitosan films values of TS ≈ 40 MPa; while %E, for low molecular weight films were 15%. Despite that, Vázquez-Briones and Guerrero-Beltrán [45] reported values of TS ≈ 5 MPa and %E = 29% for low molecular weight chitosan films, indicating that these values are related with chitosan concentration (%) employed for films elaboration.…”
Section: Mechanical Properties Evaluationmentioning
confidence: 90%
“…El consumo de infusiones del zacate limón es común en varios países desde que se descubrió el valor medicinal de la planta a lo largo de la historia (De Oliveira-E Silva et al, 2022). Diversos estudios han demostrado que algunos componentes de C. citratus presentan efectos farmacológicos y biológicos relevantes (Vázquez-Briones and Guerrero-Beltrán, 2017). Entre las actividades biológicas de esta planta se encuentran la actividad antioxidante, neuroprotectiva, antimicrobiana, antitumoral y anticancerígena (Ekpenyong, Akpan and Nyoh, 2015).…”
Section: Introductionunclassified